2017
DOI: 10.7763/ijet.2017.v9.967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Stimulation of Admixture to Workability of the Mortar

Abstract: Abstract-The objective of this research is to study the effects of thermal stimulation of PC ether high performance water-reducing agent on the workability of fresh cement-mortar. For better understanding of the behavior of these admixtures under thermal stimulation condition, two types of water-reducing agents are used, superplasticizer and high range water reducer (Air Entraining type). The chosen admixtures were heated by different temperatures, 40, 50 and 60℃ for two various times, 30 minutes and 24 hours.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…There result concluded to estimate that polymer relax and straighten by thermal stimulation. Moreover, in previous studies [7]- [10], when the more contained amount of slump keeping polymer, it was recognized that the polymer was relaxing for thermal stimulation. However, it is thought that by cooled slowly it will return to the size and geometric structure of stable polymer molecules in the state before thermal stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There result concluded to estimate that polymer relax and straighten by thermal stimulation. Moreover, in previous studies [7]- [10], when the more contained amount of slump keeping polymer, it was recognized that the polymer was relaxing for thermal stimulation. However, it is thought that by cooled slowly it will return to the size and geometric structure of stable polymer molecules in the state before thermal stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…As these results, it was confirmed that the effect of thermal stimulation and its sustainability will be improved as the content of SK type in the superplasticizer increases. In the previous studies [7][8][9][10], only fluidity of the mortar right after mixing were investigated, in this study, the effect of thermal stimulation after mixing had been evaluated. Moreover, it was confirmed that even if the initial dispersion performance improves by thermal stimulation, slump keeping performance can be maintained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat stimulation of SP increase the fluidity and air content and slightly decrease the compressive strength. [3][4]. Several factors affect the slump loss of mortar type of cement type and group of superplasticizer and amount of blast furnace slag(BFS).…”
Section: Introductionmentioning
confidence: 99%